(3TQM ebOeI GHf GdMGLH aj GdfMhs - (3YKeGf Hf YeQ Hf CHj HcQ Hf jhfS GdeGdcj GdcQOj GdCSfGFj GdeUQj , CHh YeQh LeGd GdOjf GHf GdMGLH , J (B646 (3g` s ((3MdH s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf bGd GdTjN GdeYQha HGHf GdMGLH QMeg dGdg Ydjg GdcdeI daX hGVM deYfi eaQO s
(3BNQgG (B:s
(3adG jdRe ef GYJHGQ GddGRe ddcdeI YfO YQhV MVagG GYJHGQ GdLGFR YfO YQhV GdMPa Je TQM GdebOeI s
(3hQO GdYfhGf GdCUdi ai cX (B2 / 1370s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B211 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B265s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdfMhs